2012
DOI: 10.1016/j.amepre.2012.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The Healthy Afterschool Activity and Nutrition Documentation Instrument

Abstract: Background Policies call on afterschool programs to improve the physical activity and nutrition habits of youth attending. No tool exists to assess the extent to which the afterschool program environment meets physical activity and nutrition policies. Purpose To describe the development of the Healthy Afterschool Activity and Nutrition Documentation (HAAND) instrument, which consists of two subscales: Healthy Afterschool Program Index for Physical Activity (HAPI-PA) and the HAPI-Nutrition (HAPI-N). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…In brief, the STEPs-HE conceptual framework involves a multistep, adaptive approach to incorporating healthy eating strategies into daily routine practice. The framework was informed by the authors' extensive empirical work [12][13][14][17][18][19][20] conducted within this setting, as well as their practical experience working with ASP organizations. The approach consists of identifying essential ASP characteristics that represent fundamental building blocks that function as necessary programmatic components to achieving full integration of healthy eating strategies and eventual achievement of the Healthy Eating (HE) Standards [4,5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, the STEPs-HE conceptual framework involves a multistep, adaptive approach to incorporating healthy eating strategies into daily routine practice. The framework was informed by the authors' extensive empirical work [12][13][14][17][18][19][20] conducted within this setting, as well as their practical experience working with ASP organizations. The approach consists of identifying essential ASP characteristics that represent fundamental building blocks that function as necessary programmatic components to achieving full integration of healthy eating strategies and eventual achievement of the Healthy Eating (HE) Standards [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, at baseline the Healthy Afterschool Activity and Nutrition Document (HAAND) was collected on all 20 programs. [12,17] The HAAND is collected from a single day site visit by a trained research assistant that includes direct observation of foods and beverages served, a semistructured interview with the program leader, and written document review. Only the nutrition portion of the HAAND is presented in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Inter-rater reliability (Table 2) was the most commonly tested type of reliability (n=7) 13, 21, 23-26 followed by test-retest (n=3), 21, 82, 83 and internal consistency (n=1). 25 For reliability assessment, studies reported Pearson correlation, Cronbach's α, kappa coefficient, percent agreement and/or interclass correlation coefficient (ICC) scores.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…25 For reliability assessment, studies reported Pearson correlation, Cronbach's α, kappa coefficient, percent agreement and/or interclass correlation coefficient (ICC) scores. The following tools had the highest reliability coefficients: the Wellness Child Care Assessment Tool (WellCCAT) 25 with an ICC ranging from 0.84-0.99; the Food and Beverage Environment Analysis and Monitoring System (FoodBEAM), 26 with an ICC ranging from 0.97-0.99; the Community Healthy Living Index (CHLI), 23 with percent agreement ranging from 84%-93%; and the Healthy Afterschool Activity and Nutrition Documentation (HAAND) 13 with percent agreement ranging from 85%-100% and kappa coefficients ranging from 0.73-1.00.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation